Catalytic activity of H2O2 by goethite and lepidocrocite: Insight from 5-bromosalicylic acid removal mechanism and density functional theory calculation (ID:CHEM114760). (July 2023) - Huang, Wanyi; Yuan, Yixing; Zhong, Dan; Zhang, Peng; Liangdy, Arvin; Lim, Teik-Thye; Ma, Wencheng; Yuan, Yuan
Abstract: We have compared the elimination of 5-bromosalicylic acid (BSA) in the systems of goethite (α-FeOOH)/H2 O2 and lepidocrocite (γ-FeOOH)/H2 O2 . The results demonstrated that BSA (10 mg L −1 ) could be successfully adsorbed on α- and γ-FeOOH (0.5 g L −1 ) and then effectively degraded after the addition of H2 O2 (14.7 mM). BSA adsorption on both α- and γ-FeOOH followed pseudo-second order adsorption kinetic models, with γ-FeOOH having greater adsorption ability than α-FeOOH. In the α-FeOOH/H2 O2 system, BSA degradation was well fitted with the pseudo-second order kinetics, whereas the oxidation in γ-FeOOH/H2 O2 system had a two-stage pseudo-first order kinetics. Electron paramagnetic resonance (EPR) results for these two systems revealed the presence of OH and OOH, and further tests with radical captures demonstrated their dominance in degrading BSA. Based on the electronic structure analysis, electrons were more easily transferred from the H2 O2 molecule to the Fe atoms of α-FeOOH, explaining the density functional theory (DFT) calculation results, which showed that α-FeOOH performed better in catalyzing the decomposition of H2 O2 . However, the free radicals are more likely to desorb from γ-FeOOH, which made the γ-FeOOH/H2 O2 system more efficient in degrading BSA. Graphical abstract: Image 1 Highlights: Adsorption and catalytic performance of α- and γ-FeOOH was compared. γ-FeOOH performed better in BSA removal, but relatively poor in mineralization. Potential energy reduced more when H2 O2 cracked on α-FeOOH. The energy barriers of radical desorption was lower for γ-FeOOH. Higher electronic conductivity of α-FeOOH lead to a better hybridization with H2 O2 .